The Inclusive Process of Training in social Museology: Alternative Museology in Action in Carapaterira, Portugal (Cadernos de Sociomuseologia, 2012)
Pierre Mayrand is a long-time member of ICTOP and founder of MINOM. He did graduate studies in Montreal and overseas, studying art history with a specialization in architecture and urban planning. In 1970, when the Université du Québec was founded, Pierre entered the teaching profession, participating (as director, professor, and researcher) in the setting up of programs in national heritage, museology and cultural development. He is still active in teaching and project development now as a altermuseologist.